REGENERATIVE CITIES: ECONOMIC MODELS AND FINANCIAL STRATEGIES FOR SUSTAINABLE URBAN GROWTH - Rahadi, Raden Aswin; Ria, Poeti; Hapsariniaty, Alia Widyarini; Fajar Afgani, Kurnia; Firmansyah Hakam, Dzikri (Tata Kota dan Daerah, 2025)
As urbanization accelerates amidst the escalating climate crisis, the paradigm is shifting from reactive to proactive response through regenerative urbanism. However, while the technical and ecological foundations are standardized, the economic pathways, especially in developing economies, are fragmented. This study bridges that gap by synthesizing foundational theories with recent empirical evidence (2022 – 2025) to construct a cohesive strategic framework for financing regenerative cities. Findings indicate that regenerative urbanism has evolved from a theoretical ideal into a pragmatic economic strategy applicable across diverse urban contexts. By leveraging advanced technological tools—such as AI-assissted spatial analysis and standardized valuation models—cities can now quantify and monetize “hidden” ecosystem services, transforming them into bankable assets that attract global institutional investment. Both external and internal financial instruments, such as Green Bonds and Land Value Capture (LVC), are proven applicable towards diverse urban contexts. Crucially, the research emphasizes on strong alignment between financial innovation and regulatory framework to ensure a successful regenerative urbanism transition. Policymakers must harmonize regulatory frameworks to resolve policy incoherence, ensuring that regenerative initiatives achieve substantive outcomes rather than mere procedural compliance. Ultimately, this study positions regenerative cities not just as ecological necessities, but as competitive, self-sustaining economic hubs for the future.